2017
DOI: 10.1002/syn.21964
|View full text |Cite
|
Sign up to set email alerts
|

The role of adiponectin receptors in the regulation of synaptic transmission in the hippocampus

Abstract: In the last two decades adiponectin, member of the adipokines family, gained attention because of its unique antidiabetic effects. However, the presence in the brain of adiponectin receptors and adiponectin itself raised interest because of the possible association with neuropsychiatric diseases. Indeed, clinical studies found altered concentration of adiponectin both in plasma and cerebrospinal fluid in seeveral pathologies including depression, multiple sclerosis, Alzheimer's disease and stroke. Moreover, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
1
14
1
Order By: Relevance
“…Furthermore, adiponectin applied 10 minutes prior to stimulation protocols potentiates LTP via high-frequency stimulation and prevents induction of long-term depression (LTD) via low-frequency stimulation, suggesting that adiponectin may play a role in both LTP and LTD. In contrast to the DG, in the cornu ammonis 1 (CA1) region of the hippocampus, the adiponectin receptor agonist AdipoRon reduces LTP [ 112 ], suggesting subregional variation in adiponectin responses. In addition, these studies found subregion-specific alterations in paired pulse facilitation, indicating potential presynaptic mechanisms of adiponectin signaling.…”
Section: Adiponectin and Alzheimer's Diseasementioning
confidence: 99%
“…Furthermore, adiponectin applied 10 minutes prior to stimulation protocols potentiates LTP via high-frequency stimulation and prevents induction of long-term depression (LTD) via low-frequency stimulation, suggesting that adiponectin may play a role in both LTP and LTD. In contrast to the DG, in the cornu ammonis 1 (CA1) region of the hippocampus, the adiponectin receptor agonist AdipoRon reduces LTP [ 112 ], suggesting subregional variation in adiponectin responses. In addition, these studies found subregion-specific alterations in paired pulse facilitation, indicating potential presynaptic mechanisms of adiponectin signaling.…”
Section: Adiponectin and Alzheimer's Diseasementioning
confidence: 99%
“…Cognitive decline in AD is attributed to synaptic dysfunction in the hippocampus 11 , related to a loss of long-term potentiation (LTP), a molecular mechanism of hippocampal synaptic plasticity 1214 . Adiponectin treatment was shown to enhance synaptic function 15 and promote presynaptic release 16 , and increases in circulating adiponectin levels alleviate memory dysfunction in models of dementia 5,17 . To evaluate the effects of adiponectin on hippocampal LTP as well as the mobility of cell surface ionotropic glutamate receptors in AD, we utilised a mouse model harbouring five familial AD mutations, the 5XFAD mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adiponectin acts using three different receptors: AdipoR1, AdipoR2 and T‐cadherin . The different effects elicited by adiponectin are probably mediated by the distinct oligomers of this protein as well as by the different receptors .…”
Section: Introductionmentioning
confidence: 99%